Herramienta Cacao (Cocoa Tool): Original song by Uri Guevara Lopez (Waslala, Nicaragua) - International Center for Tropical Agriculture (2016)
Inspired by the work led by the CGIAR Research Program on Integrated Systems for the Humid Tropics (Humidtropics) through CIAT, to develop a toolkit that strengthens decision-making processes at farm level in the municipality of Waslala, Nicaragua, members of the territorial organization APROMUWA share their experience as participants of this project through a song.